Preparation and Characterization of Different Types of Extruders and Its Techniques - Ogale, Nikita; Kamble, Komal (Asian Journal of Pharmaceutical Research and Development, 2021)
The study on characterization of different types of extruder such as single screw cone type, axial type extruder, radial type extruder, die roller type extruder from excipient, enzyme and silica has been performed. The primary goal of the project focuses on making pellets from MCC+LACTOSE, MCC+STARCH, Enzyme and Silica. The process is extremely encouraged in several pharmaceutical industries. The below article will help us understand various aspects of techniques used in the extrusion of pellets. The extruder process of pellets are mainly mixing and extrusion. We will also discuss about the several factors that might influence the pellet quality which includes formulation - granulating liquid, excipients; Equipment (Rapid mixer granulator, various type of extruder, and size of extrusion screen) and process (Extrusion speed, extrusion time). The characterization of the pellets includes estimation of various parameters such as moisture content ,appearance, shape , bulk density, disintegration of the pellets are explained.